Réponses

Meilleure réponse !
2014-05-22T21:31:12+02:00
a )
- 2x + 7 = 12
- 2x = 12 - 7
- 2x = 5
x = - 5/2

b)
- 2 + 3y = - 6
3y = - 6 + 2
3y = - 4
y = - 4/3

c)
5 - 2a = 12
- 2a = 12 - 5
- 2a = 7
a = - 7/2

d)
3/2t = 1/2 - 5/2
3/2t = - 4/2
t = -4/2 x 2/3
t = -8/6
t = -4/3

e)
3x + 7 = x + 2
3x - x = 2 - 7
2x = - 5
x = - 5/2

f)
2 + 2y = -1 + 3y
2y - 3y = - 1 - 2
- y = - 3
y = 3

g)
4 - 5a = 2a - 1
- 5a - 2a = - 1 - 4
- 7a = - 5
a = 5/7

h)
t - 4 = - 3t - 10
t + 3t = - 10 + 4
4t = - 6
t = - 6/4
t = - 3/2